2010
DOI: 10.1001/archdermatol.2010.191
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Laser Scanning Microscopy vs 3-Dimensional Histologic Imaging in Basal Cell Carcinoma

Abstract: To compare ex vivo confocal laser scanning microscopy (CLSM), which offers rapid images without the need for tissue processing, vs 3-dimensional histologic imaging, the criterion standard treatment for basal cell carcinomas in high-risk areas of the face.Design: Single-center prospective trial.Setting: Dermatosurgical unit of a university hospital.Patients: Seventy-two consecutive surgically removed basal cell carcinomas were examined using CLSM vs standard paraffin-embedded 3-dimensional histologic imaging.In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 19 publications
(33 reference statements)
0
38
0
1
Order By: Relevance
“…It can be used for diagnostic purposes as well as for monitoring treatment efficacy, resolution, or recurrence. Ziefle et al compared the use of confocal laser microscopy versus histological imaging in detecting excised BCC [23]. The sensitivity and specificity of BCC detection varied across different histological sections including midsections, lateral margins, muffins and bread loaf sections.…”
Section: • Multispectral Fluorescence Lifetime Tomographymentioning
confidence: 99%
“…It can be used for diagnostic purposes as well as for monitoring treatment efficacy, resolution, or recurrence. Ziefle et al compared the use of confocal laser microscopy versus histological imaging in detecting excised BCC [23]. The sensitivity and specificity of BCC detection varied across different histological sections including midsections, lateral margins, muffins and bread loaf sections.…”
Section: • Multispectral Fluorescence Lifetime Tomographymentioning
confidence: 99%
“…One study on 45 excisions reported sensitivity and specificity values of 97 and 89%, respectively, which were confirmed in another study. Since the duration of the CLSM examination was only about 7.5 min, the use of this method promises an acceleration of those surgical procedures [11,12].…”
Section: Basal Cell Carcinomamentioning
confidence: 99%
“…Recently, ex vivo fluorescence confocal microscopy (FCM) has been employed as an innovative tool that can provide a fast imaging of the fresh tissue with no need of any staining or special sample preparation that may require a dedicated laboratory technician [3,4,5,6,7,8,9,10,11,12,13,14,15,16]. Compared to in vivo confocal microscopy, FCM permits the analysis of freshly excised tumor allowing the assessment of deep margins with higher resolution because of the employment of fluorescent agent contrast.…”
Section: Introductionmentioning
confidence: 99%